ANALYSIS OF FACTORS THAT INFLUENCE CAREER CHOICE AS A PUBLIC ACCOUNTANT WITH MOTIVATION AS A MODERATING VARIABLE: (Study on Undergraduate Accounting Study Program Students of Udayana University) - Vemiyani, Ni Made Dhea; Suartana, I Wayan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Indonesia faces a critical shortage of public accountants despite a growing demand for their services. While many individuals graduate with accounting degrees, few pursue careers in public accounting. This research aimed to understand the factors influencing this career choice, specifically examining the roles of financial rewards, professional recognition, and work environment, as well as the moderating effect of motivation. Based on expectation and planned behavior theories, the study analyzed data from 74 participants at Udayana University. Results indicate that motivation significantly impacts the relationship between financial rewards and the decision to become a public accountant, but it does not influence the relationships between professional recognition, work environment, and career choice in this field.